Is PNF Really Better than Walking Recovery? - Putri, Orchidhea; Fatkur Rohman Kafrawi; Ananda Perwira Bakti; Indra Himawan Susanto (Universitas PGRI Palembang, 2024)
The pulse rate gradually increases depending on the intensity of the activity performed and can potentially cause fatigue. Walking recovery and PNF (Proprioceptive Neuromuscular Facilitation) can lower the pulse rate and prevent fatigue. The research aims to prove the effects and differences resulting from walking recovery and PNF. The study uses a pretest and posttest design with impact and difference tests. Ten samples were selected purposively and underwent two recovery interventions. A 1600-meter run protocol was used to increase the pulse rate. The results showed that walking recovery could reduce the pulse rate by up to 15.49%, while passive recovery reached 29.35%. Each recovery method significantly reduced the pulse rate (p < 0.05), but there was no significant difference between the two recovery methods (p > 0.05).